A function g in terms of f wherein the function g is a reflection in the y-axis of the graph of f can be written as g(x) = f(-x). With this expression, we can see that for a given x-value, the y-value would have an opposite sign. Take for example, let f = 2x. We construct a table to show the resulting x and y values.
x f(-x) g(x)
-2 2(2) = 4 2(-2) = -4
-1 2(1) = 2 2(-1) = -2
0 2(0) = 0 2(0) = 0
1 2(-1) = -2 2(1) = 2
2 2(-2) = -4 2(2) = 4
Plotting the points of functions f and g would show that the graph of the function g reflects function f about the y-axis.